Data encryption using N-lag white multisine random time-series - Niederliński, Antoni; Figwer, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
A new data encryption method based on N-lag white multisine random time-series (WMRTS) is presented. Its essence is that consecutive characters of the cleartext are used to generate phase shifts for all or for some of the sine components of an N-lag WMRTS. This time-series is defined in the frequency domain by its Discrete Fourier Transform (DFT). It consists of two spectra: the phaseshift spectrum containing encrypted characters and the amplitude spectrum with the same amplitude for all frequencies.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka